Reconstructing a Core Literacy-Aligned Primary School Labor Education Curriculum System: Barriers and Systemic Solutions - Wu, Meijun (Education Insights, 2026)
With the global shift towards cultivating twenty-first-century core competencies, labor education has increasingly become a fundamental cornerstone of holistic education systems worldwide. In China, the comprehensive 2022 curriculum reform officially elevated labor education to the status of an independent, compulsory course, reflecting a profound national commitment to fostering practical skills and moral development among young learners. However, despite these progressive policy advancements, significant structural deficiencies within the current curriculum design have substantially hindered its practical effectiveness and overall pedagogical impact. This paper systematically constructs a robust theoretical framework that intricately links the principles of core literacy with the foundational goals of primary school labor education. Through rigorous analysis, the study identifies three key implementation barriers currently impeding progress: highly fragmented educational objectives that lack cohesive progression, severely decontextualized instructional content that fails to resonate with students' lived experiences, and disjointed evaluation mechanisms that inadequately measure genuine competency acquisition. To address these critical challenges, this research proposes a comprehensive, four-dimensional systemic reconstruction path designed to seamlessly integrate labor education into the broader academic ecosystem. By realigning curriculum standards, optimizing pedagogical strategies, enriching contextual learning environments, and establishing authentic assessment rubrics, the proposed model ensures a more cohesive educational experience. Ultimately, the findings provide highly actionable, evidence-based strategies to significantly improve primary school labor education in China, while simultaneously offering valuable theoretical insights and practical paradigms for global educational reform initiatives focused on holistic student development.